Efektivitas Metode Drill terhadap Keterampilan Teknik Dasar Tendangan Lurus Pencak Silat Ekstrakurikuler SMPN 1 Tirtajaya - Badru Maulana; Akhmad Dimyati; Rhama Nurwansyah Sumarsono; Irfan Zinat Achmad (Universitas Hamzanwadi, 2026)
This study was motivated by the low level of pencak silat straight-kick skills among extracurricular participants, as evidenced by suboptimal balance, accuracy in the direction of the kick, and final posture. This study aims to determine the effectiveness of the drill method on straight kick skills in pencak silat. The study used a quantitative approach with an experimental method and a one-group pretest-posttest design. The study population consisted of all pencak silat extracurricular participants at SMPN 1 Tirtajaya, with a sample of 15 participants selected using total sampling. The research instrument consisted of a straight kick skill assessment sheet covering the aspects of initial stance, preparatory stance, execution, and final stance. Data were analyzed using descriptive statistics, a normality test, and a paired-sample t-test with the aid of SPSS version 27. The results showed that the mean score for straight kick skills increased from 9.07 on the pretest to 11.87 on the posttest. The results of the normality test showed that the data were normally distributed, with a significance value of 0.539 for the pretest and 0.413 for the posttest. The results of the paired-sample t-test showed a significance value of 0.000 (<0.05), indicating a significant improvement in straight-kick skills following the intervention. Thus, the drill method is effective in improving straight-kick skills in pencak silat.